An Attempt to Design a Business Capstone Course: A Personal Experience - Issa, Theodora (Common Ground, 2013)
Derived from a personal experience, this paper presents a framework on how a ‘Capstone Course’ might be developed at a university in Australia. This paper begins with a selective literature review on the diverse ideas and methods of teaching a ‘Capstone Course’ at different levels and disciplines, then discusses the process followed to have the course syllabus and outcomes approved by top management. The literature will shed some light on the ways by which this course is delivered at business schools in different parts of the world at various levels. A common theme in the literature is that, regardless of the diverse ways in which this course can be delivered, the syllabus must be relevant to real-life situations and actual business practices. This is a difficult task since differences are apparent regarding the contents of this course and the diverse views regarding the sort of relationship that a university should have with businesses. Indeed, in obtaining necessary approvals as to how this course can be delivered, there are both challenges and limitations. This paper reports on a personal experience in developing such a course, highlighting the great opportunities and the immense challenges faced by the developer. This paper shares with readers a ‘theoretical’ vision rather than a ‘practical’ implementation of a Capstone Course designed for inter disciplinary business students in Australia. This paper highlights the challenges and limitations experienced, with suggestions and steps depicted in a conceptual model as to how best a ‘Business Capstone’ course can be designed and implemented to achieve the ultimate goal of preparing students for the real world.